Redescription and taxonomic status of Dipturus chilensis (Guichenot, 1848), and description of Dipturus lamillai sp. nov. (Rajiformes: Rajidae), a new species of long-snout skate from the Falkland Islands - Concha, Francisco J.; Caira, Janine N.; Ebert, David A.; Pompert, Joost H. W. (Zootaxa, 2019)
Recent molecular evidence has called into question the identity of skates collected in the waters off the Falkland Islands previously identified as Zearaja chilensis. NADH2 sequence data indicate that these specimens are not conspecific with those currently referred to as Z. chilensis from Chile and, in fact, represent a novel cryptic species. This study aimed to investigate this hypothesis based on morphological comparisons of specimens from the coasts of both western and eastern South America. In total, 50 specimens from Chile and 41 specimens from the Falkland Islands were collected and examined; morphometric data were generated for a subset of specimens from both areas. NADH2 sequence data were generated for a total of 19 specimens from both areas, as well as specimens of Z. nasuta from New Zealand, D. pullopunctatus from South Africa, D. oxyrinchus from the Azores, Okamejei hollandi, and O. cairae from Borneo, and O. kenojei from Japan. Based on morphological and molecular analyses, Zearaja is synonymized with Dipturus and species assigned to the former genus are transferred to the latter genus. A neotype is designated for D. chilensis and this species is redescribed. Dipturus lamillai sp. nov. is described based on specimens from the Falkland Islands. Comparison of our NADH2 data with data for mitochondrial genomes generated from tissue samples taken from two specimens originally identified as Z. chilensis, indicate that, while the sample from Chile came from a specimen of D. chilensis, that from the skate steak obtained from a restaurant in Korea actually came from a specimen of D. lamillai sp. nov. This emphasizes the importance of confirming both the provenance and identity of specimens from which sequence data are generated and submitted to GenBank if misidentifications are to be avoided.